1998
DOI: 10.1038/bjc.1998.550
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of interleukin 15 and interleukin 2 for induction of killer activity and of type 2 cytokine production by mononuclear cells from lung cancer patients

Abstract: Summary Interleukin (IL) 15 is a novel cytokine with IL-2-like activity. In this study, we examined the effect of IL-15 on induction of non major histocompatability complex (MHC)-restricted killer activity and of type 2 cytokine production by peripheral blood and pleural mononuclear cells (MNCs), from 34 lung cancer patients and 20 control subjects. Interleukin 15 (IL-15) is a novel M 15 000 cmtokine and has similar biological activities to those of IL-2: it induces T-cell proliferation. enhances natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In the setting of tumor and HIV immunotherapy, IL-15 provides hope that where T cell responses to IL-2 are inefficient or defective they can be reactivated (29,30). However, administration of IL-15 to patients is potentially risky, as IL-15 is implicated in the pathogenesis of autoimmune diseases such as rheumatoid arthritis (31), and in the case of MM, potentially could act as a tumor cell survival factor (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of tumor and HIV immunotherapy, IL-15 provides hope that where T cell responses to IL-2 are inefficient or defective they can be reactivated (29,30). However, administration of IL-15 to patients is potentially risky, as IL-15 is implicated in the pathogenesis of autoimmune diseases such as rheumatoid arthritis (31), and in the case of MM, potentially could act as a tumor cell survival factor (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…IL-15, a novel cytokine initially identified in culture supernatants of the kidney epithelial cell line CV-I/EBNA, stimulates proliferation, activation and recruitment of T and B cells, natural killer (NK) cells and lymphokine-activated killer cells through interaction with components of the IL-2Rβ and γ chains in addition to its unique binding protein (IL-15Rα) [10, 11, 12, 13, 14, 15, 16]. Unlike IL-2, IL-15 gene expression has been reported in various tissues and cells including lung adenocarcinoma cell line [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tumor cells engineered to secrete IL-15 were found to increase anti-tumor immune responses in vivo (36). Takeuchi and colleagues have studied IL-15-induced human killer cell activity against lung cancer cell lines and concluded that this cytokine has the potential for lung cancer immunotherapy (37). One study has compared the toxicity and anti-tumor efficacy of IL-15 with IL-2 in the context of syngeneic bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…This attests to the complexity of the biological activity of IL-15. On one hand, this cytokine may possess some anti-tumor properties (11,12), whereas, on the one other hand, it may also possess proinflammatory properties (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation